2019
DOI: 10.4103/ajns.ajns_220_18
|View full text |Cite
|
Sign up to set email alerts
|

Superficial temporal artery: Middle cerebral artery bypass, our series of 20 cases, surgical technique and indications with illustrative cases

Abstract: The first extracranial-intracranial (EC-IC) bypass surgery was performed by professor Yasargil in 1967 since then this procedure has been widely used in vascular neurosurgery and sometimes, in tumors excision when a vascular sacrifice is necessary. In this article, we will illustrate the surgical technique of the superficial temporal artery-middle cerebral artery (STA-MCA) bypass with two cases; a 59-year-old male and 64-year-old female who presented with an occlusion of the MCA. The male presented also with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
3
0
5
Order By: Relevance
“…Technika ta została wprowadzona przez Yasargila w późnych latach 60. XX wieku [24,25] i od tego czasu jest powszechnie stosowana w neurochirurgii [26]. Zabieg zespolenia obu wymienionych tętnic pozwala na zwiększenie przepływu krwi w obszarach objętych niedokrwieniem z powodu obecności zwężonych, niedrożnych naczyń.…”
Section: Technika Sta-mcaunclassified
See 3 more Smart Citations
“…Technika ta została wprowadzona przez Yasargila w późnych latach 60. XX wieku [24,25] i od tego czasu jest powszechnie stosowana w neurochirurgii [26]. Zabieg zespolenia obu wymienionych tętnic pozwala na zwiększenie przepływu krwi w obszarach objętych niedokrwieniem z powodu obecności zwężonych, niedrożnych naczyń.…”
Section: Technika Sta-mcaunclassified
“…Zabieg zespolenia obu wymienionych tętnic pozwala na zwiększenie przepływu krwi w obszarach objętych niedokrwieniem z powodu obecności zwężonych, niedrożnych naczyń. Metoda ta jest wykorzystywana w leczeniu MMD, ale i również w niektórych operacjach tętniaków, w przypadku urazów tętnicy środkowej mózgu podczas operacji czy też guzów podstawy czaszki [25,26]. Przed wykonaniem zabiegu STA-MCA sugeruje się włączenie farmakoterapii przeciwkrzepliwej w celu uniknięcia powikłań zakrzepowych [25].…”
Section: Technika Sta-mcaunclassified
See 2 more Smart Citations
“…One such procedure is the cerebral bypass. Any brain surgeon dealing with cerebral vasculature requires precise actions while navigating the blood vessels on the exterior surface of the temporal lobe [ 1 ], microanastomosis skills, familiarity with the shape and volume of the vessels, and the ability to use instruments properly for basic vessel repairment or complex revascularization procedures [ 2 ]. A recent study has demonstrated that the number of cerebral bypasses performed for adult revascularization has increased in the United States between the years 2002 and 2014.…”
Section: Introductionmentioning
confidence: 99%